The Concept of Neutrality with Regard to Gender and Religion - Mügge, Cornelia (Enthalten in:Religion & gender;Leiden : Brill, 2011;5(2015), 2, Seite 150-164;Online-Ressource, 2015)
This article is about the meaning and the plausibility of the concept of neutrality with regard to debates on gender and religion in political philosophy. As an example, it takes the Capabilities Approach of Martha Nussbaum, which is particularly instructive as she advocates neutrality between comprehensive doctrines and, at the same time, attends to the challenges posed by gender and religion. Starting from an explanation of the meaning of the concept of neutrality in Nussbaum’s approach, the article focuses on objections against neutrality raised by feminist approaches. It discusses Nussbaum’s defence of neutrality and asks whether it is convincing or not, and to what extent. The article suggests a differentiation between neutrality as an ideal and the attribution of neutrality to actual political norms. It further argues that, whereas Nussbaum’s approach implies the latter conception, the former better corresponds to the basic norm of equal respect.
10.18352/rg.10120
Keywords: Martha Nussbaum; Political philosophy; feminist ethics; secularism